2002
DOI: 10.1002/sim.1147
|View full text |Cite
|
Sign up to set email alerts
|

An empirical comparison of record linkage procedures

Abstract: We consider the problem of record linkage in the situation where we have only non-unique identifiers, like names, sex, race etc., as common identifiers in databases to be linked. For such situations much work on probabilistic methods of record linkage can be found in the statistical literature. However, although many groups undoubtedly still use deterministic procedures, not much literature is available on deterministic strategies. Furthermore, there appears to exist almost no documentation on the comparison o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 19 publications
(27 reference statements)
2
67
0
3
Order By: Relevance
“…Previous research suggests that the positive predictive value of all three linkage algorithms used in this research would in the low to high 90s Gomatam & Carter, 1999;Gomatam et al, 2002;Grannis et al, 2002) and that sensitivity is likely to range from the mid-80s (match-merge) to the mid-90s (probabilistic).…”
Section: Linkage Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…Previous research suggests that the positive predictive value of all three linkage algorithms used in this research would in the low to high 90s Gomatam & Carter, 1999;Gomatam et al, 2002;Grannis et al, 2002) and that sensitivity is likely to range from the mid-80s (match-merge) to the mid-90s (probabilistic).…”
Section: Linkage Methodsmentioning
confidence: 81%
“…The FOP has adopted a Common Patient Identifier (CPI) constructed from the following data elements: gender, birth date, birthplace, first 3 characters of first name, and first 3 characters of last name. More complex deterministic algorithms are discussed in the literature Gomatam et al, 2002;Grannis et al, 2002).…”
mentioning
confidence: 99%
“…In practise, therefore, deterministic rule based systems are limited to ad-hoc linkages of smaller data sets. In a recent study [20] an iterative deterministic linkage system has been compared with the commercial probabilistic system AutoMatch [27]. Empirical results showed that the probabilistic approach resulted in better linkage quality.…”
Section: Deterministic Linkagementioning
confidence: 99%
“…Two general strategies are used for these designations: deterministic and probabilistic (Fellegi & Sunter, 1969;Gomatam, Carter, Ariet & Mitchell, 2002;Jaro, 1995). Deterministic linkage strategies examine the number of agreeing identifiers in a pair of records and designate the one with the most agreements (above a minimum number of agreements) as the matching pair; all other pairs are non-matches.…”
Section: Classificationmentioning
confidence: 99%